Investment market in China: current and perspectives - Koliesnichenko, Anastasiia; Yuying, Deng (Національний технічний університет "Харківський політехнічний інститут", 2024)
The investment market in China stands as a beacon of potential amidst a sea of emerging economies. Characterized by a dynamic blend of opportunities and challenges. While the investment market in China offers a fertile ground for growth and innovation, it is not without its challenges. As the country continues on its path of economic reform and development, the investment market is expected to become increasingly attractive to both domestic and international investors, heralding a new chapter in the nation's economic narrative.
Keywords: investment market; investors; perspectives; challenges